2020
DOI: 10.7554/elife.58139
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific effects of cooperative breeding and colonial nesting on prosociality in corvids

Abstract: The investigation of prosocial behavior is of particular interest from an evolutionary perspective. Comparisons of prosociality across non-human animal species have, however, so far largely focused on primates, and their interpretation is hampered by the diversity of paradigms and procedures used. Here we present the first systematic comparison of prosocial behavior across multiple species in a taxonomic group outside the primate order, namely the bird family Corvidae. We measured prosociality in 8 corvid spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(72 citation statements)
references
References 100 publications
5
66
1
Order By: Relevance
“…All of the transfers occurred in the non-social control condition and were transferred either to an empty compartment or through the outer wire mesh of the aviary, where no potential recipients were present in both cases. This result contradicts our main hypothesis that the crows and magpies would behave prosocially towards their group members, as has been observed in the wild [31,32] and demonstrated experimentally in captive birds in the group service paradigm for both species [45,55] and in a naturalistic food provisioning experiment with azure-winged magpies [39]. Given that prosocial behavior has been shown to depend on the context and/or on the specific group, when tested in other non-human animals (e.g., chimpanzees [11,61,62]), it is possible that the subjects were not motivated to act prosocially in the context of the current experiment.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…All of the transfers occurred in the non-social control condition and were transferred either to an empty compartment or through the outer wire mesh of the aviary, where no potential recipients were present in both cases. This result contradicts our main hypothesis that the crows and magpies would behave prosocially towards their group members, as has been observed in the wild [31,32] and demonstrated experimentally in captive birds in the group service paradigm for both species [45,55] and in a naturalistic food provisioning experiment with azure-winged magpies [39]. Given that prosocial behavior has been shown to depend on the context and/or on the specific group, when tested in other non-human animals (e.g., chimpanzees [11,61,62]), it is possible that the subjects were not motivated to act prosocially in the context of the current experiment.…”
Section: Discussioncontrasting
confidence: 99%
“…However, in these prosocial choice studies, it was not clear how acquiring the task contingencies, the visibility of food, and the donors’ attention influenced prosocial performance [ 1 ]. Horn and colleagues [ 45 ] tested eight corvid species in the group service paradigm, in which the birds were tested in their regular social groups and could choose to provide food to their group members by landing on a simple seesaw apparatus. The authors found high rates of prosocial food deliveries in three corvid species (azure-winged magpies, carrion crows, and one group of New-Caledonian crows).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This repurposing of ancient neural circuits is analogous to ancient architects who easily repurposed old structures for new purposes. For (Horn et al, 2020) example, in 1453 the Ottoman Empire constructed a magnificent Islamic grand mosque in Istanbul simply by modifying the preexisting Hagia Sophia cathedral originally constructed over 1000 years earlier by Emperor Constantine. Evolution appears to take similarly easy routes.…”
Section: Evolution Of Novel Social Behaviorsmentioning
confidence: 99%
“…Alternative hypotheses for the evolution of prosocial behaviors have been proposed based on observations in primates and corvids (Horn et al, 2020). The cooperative breeding hypothesis proposes that prosocial behaviors (i.e., sharing food with non-kin) evolved from through expansion of psychological processes regulating alloparental care in cooperative breeding species.…”
Section: Evolution Of Novel Social Behaviorsmentioning
confidence: 99%